Fitoquímica e atividade anti-inflamatória de Costus Spiralis (Jacq.) Roscoe - Tais Azevedo Garcia (2011)
Costus spiralis (Jaqc) Roscoe (Costaceae), popularly named cana do brejo, is traditionally used in Brazil to treat kidney affections. The anti-inflammatory activity of an ethanol extract from C. spiralis leaves, fractions and a compound isolated from it were evaluated by using a model of carrageenan-induced paw edema in Swiss mice. The extract was assayed per os at the doses of 10, 100 and 1000 mg/kg and presented antiedematogenic activity at all doses, thus confirming the ethnopharmacological use of the species. The crude ethanol extract from C. spiralis leaves was submitted to silica gel column chromatography affording fractions Hex, Hex: DCM (1:1), DCM, DCM: EtOAc (1:1), EtOAc, EtOAc: MeOH (1:1) and MeOH. The obtained fractions were assayed per os in the carrageenan induced paw edema model, at the doses of 5, 50 and 500 mg/kg. The Hex and EtOAc:MeOH (1:1) fractions showed antiedematogenic activity. The EtOAc:MeOH (1:1) was submitted to fractionation by reverse phase high performance liquid chromatography resulting in the isolation of a solid named FLAV1. Analyses of spectrometric data recorded for FLAV1 were compatible with four isomeric flavones: schaftoside, isoschaftoside, neoschaftoside and neoisoschaftoside. The antiedematogenic activity of FLAV1 was evaluated by using the carrageenan induced paw edema model in Swiss mice, at the doses of 0.5, 1.0 and 2.0 mg/kg administered by intraperitoneal injection. FLAV 1 ellicited antiedematogenic response at the higher doses (1 and 2 mg/Kg), suggesting its participation in the anti-inflammatory activity of C. spiralis and, therefore, that it may represent a chemical marker for the species. A spectrophotometric method was validated for the quantitative determination of total flavonoids in a commercial extract of C. spiralis. The extract present 0,795% of total flavonoids, expressed as quercetin.